Wiley-Blackwell companion to Chinese religions - Nadeau, Randall L. (Wiley-Blackwell companions to religion, 2012)
Comprising the most up-to-date, interdisciplinary research on the study of Chinese religious beliefs and cultural practices, this volume explores the rich and complex religious and philosophical traditions that have developed and flourished in one of the world's oldest civilizations. Covers the main Chinese traditions of Confucianism, Taoism, and Buddhism as well as Christianity and Islam. Features a unique organizational structure, with groups of readings focused on historical, traditions-based, and topical elements of Chinese religion. Explores a number of contemporary religious topics